ANALISIS PENENTUAN BIAYA PRODUKSI BERDASARKAN SISTEM BIAYA BERBASIS AKTIVITAS (ABC) PADA USAHA KERIPIK KELADI BINTANG TIMUR - Kurniawati, Dinar; Resi, Yohanes Damaskus; Lambi, Manuel (JURNAL LENTERA BISNIS, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening Indonesia’s economic foundation, particularly in West Papua, which is experiencing rapid regional growth. One of the local food-based MSMEs contributing to this development is Keripik Keladi Bintang Timur Enterprise located in Manokwari Regency. However, the business faces challenges in accurately determining production costs because it still applies a traditional volume-based costing method that does not reflect the real consumption of production activities. This study aims to analyze the determination of production costs using the Activity-Based Costing (ABC) system to produce more accurate and reliable cost information. A quantitative descriptive approach was applied using primary data obtained through interviews, observation, and documentation from January to June 2025. The main production activities identified include raw material preparation, frying, packaging, and distribution, each with distinct cost drivers. The analysis revealed that the total monthly production cost amounted to Rp7,250,000, with a unit cost of Rp36,250 under the traditional method and Rp34,750 under the ABC method. The difference of Rp1,500 per unit indicates that the ABC method provides more precise cost allocation based on actual resource consumption. The study also found that raw material preparation and frying activities account for more than 60% of the total cost, suggesting that efficiency improvements should focus on these stages. Overall, the ABC method proves to be a relevant and adaptive approach for MSMEs, enhancing cost transparency and supporting rational pricing decisions for local food-based enterprises.